The Art of Community: Building the New Age of Participation - Bacon, Jono (O'Reilly Media, 2012)
Online communities provide a wide range of opportunities for supportin g a cause, marketing a product or service, or building open source sof tware. The Art of Community helps you recruit members, motivate them, and manage them as active participants. Author Jono Bacon offers exper iences and observations from his 14-year effort to build and manage co mmunities, including his current position as manager for Ubuntu.Discov er how your community can become a reliable support network, a valuabl e source of new ideas, and a powerful marketing force. This expanded e dition shows you how to keep community projects on track, make use of social media, and organize collaborative events. Interviews with 12 co mmunity management leaders, including Linus Torvalds, Tim O’Reilly, an d Mike Shinoda, provide useful insights.Develop specific objectives an d goals for building your communityBuild processes to help contributor s perform tasks, work together, and share successesProvide tools and i nfrastructure that enable members to work quicklyCreate buzz around yo ur community to get more people involvedHarness social media to broadc ast information, collaborate, and get feedbackUse several techniques t o track progress on community goalsIdentify and manage conflict, such as dealing with divisive personalities